Plant stress biology in epigenomic era. (May 2020) - Perrone, Anna; Martinelli, Federico
Highlights: Different DNA methylation enzymes are involved in different plant processes. An integrated systems biology approach is needed in crop stress biology. Priming drives a wide range of epigenetic mechanisms. An epigenetic code is present in response to environmental stresses in plants. Abstract: Recent progress in "omics" methodologies allow us to gain insight into the complex molecular regulatory networks underlying plant responses to environmental stresses. Among the different genome-wide analysis, epigenomics is the most under-investigated "omic" approach requiring more critical and speculative discussion about approaches, methods and experimental designs. Epigenomics allows us to gain insight into the molecular adaptation of plants in response to environmental stresses. The identification of epigenetic marks transmitted during filial generations enables new theories to be developed on the evolution of living organisms in relation to environmental changes. The molecular mechanisms driving the capacity of plants to memorize a stress and to generate stress-resistant progenies are still unclear and scarcely investigated. The elucidation of these cryptic molecular switches will assist breeders in designing crops characterized by minimally compromised productivity in relation to stresses caused by climate change. The aim of this review is to briefly describe the most uptodate epigenomic approaches, update recent progresses in crop epigenomics in plant stress biology, and to stimulate the discussion of new epigenomic methods and approaches in the new era of "omic" sciences.